2014
DOI: 10.1016/j.euroneuro.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion response on sleep quality in patients with depression: Implications for increased cardiovascular disease risk

Abstract: Depression could be an independent risk factor for cardiovascular disease. We assessed bupropion response in depressed patients by polysomnography (PSG) and cardiopulmonary coupling (CPC) variables. Nineteen subjects participated in a two-session, two consecutive night PSG protocol. Participants received either placebo or bupropion-SR 150 mg, orally, in a randomized, double-blind cross-over fashion on night two. Outcome variables were: sleep stages, REM latency, stable, unstable sleep and very low frequency co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In a study with 126 patients with MDD, was found that increased BDFN levels has been associated with N-REM sleep improvement and enhanced slow wave activity, but on the other hand, reported no relationship between BDFN and insomnia improvement. It was found that the reduction of BDFN levels is associated with improvement in hypersomnia [ 16 ].…”
Section: Bdnf and Sleepmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study with 126 patients with MDD, was found that increased BDFN levels has been associated with N-REM sleep improvement and enhanced slow wave activity, but on the other hand, reported no relationship between BDFN and insomnia improvement. It was found that the reduction of BDFN levels is associated with improvement in hypersomnia [ 16 ].…”
Section: Bdnf and Sleepmentioning
confidence: 99%
“…Giese and cols investigated if stress levels influence the association between sleep and BDNF levels, and found that the sleep quality interfere directly in the relation of stress with BDNF levels [ 16 ]. In another study they investigated BDNF serum levels in 26 patients with insomnia and compared the results with a control group and found that insomniacs present decreased serum BDNF levels, when compared to control group [ 28 ].…”
Section: Bdnf and Sleepmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, depression has been found to predict early onset CHD. Depression could be an independent RF for CVD and it is common among pts treated with PCI [64,65]. Numerous psychosocial factors have been linked to CHD [66].…”
Section: Discussionmentioning
confidence: 99%